Improving the Ability of Teachers of SMPN 3 Batukliang, Central Lombok Regency in Class Action Research (CAR) - Susilawati Susilawati; Aris Doyan; Hairunnisa Sahidu; Hikmawati Hikmawati; Ahmad Harjono (Unram Journal of Community Service, 2022)
Classroom Action Research (CAR) is a very important method in improving teacher performance and professionalism. Classroom Action Research can improve the learning process and does not interfere with the teacher's task in learning at school. However, the limited knowledge of teachers regarding procedures for preparing CAR, models, strategies, learning methods that can be applied in learning, as well as proper data collection, processing, and analysis are obstacles that are often encountered in the field. Therefore, various efforts have been made to improve teacher performance in improving teacher professionalism, namely by holding an activity in the form of socialization to assist teachers in preparing Classroom Action Research (CAR). The results of the service carried out showed that the socialization material was delivered very clearly and the participants were able to understand the material presented well. It is hoped that this activity can foster the habit of researching and pouring out the results of their research in the form of scientific works to teachers. In addition, teachers have confidence in carrying out their duties and obligations. So, with the implementation of classroom action research (CAR).